BiOCl / UiO-66 (Zr / Ce) heterojunction photocatalyst as well as preparation method and application thereof
By introducing Ce in UiO-66 (Zr) and building a BiOCl/UiO-66 (Zr/Ce) heterojunction, the shortcomings of BiOCl photocatalyst in visible light capture and carrier migration efficiency were solved, and efficient photocatalytic oxidation performance and tetracycline degradation efficiency were achieved.
Patent Information
- Application Number
- CN202411646008.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-25
AI Technical Summary
BiOCl photocatalysts have limitations on the problems of insufficient visible light capture capability, low carrier migration efficiency, and structural stability affected by photocorrosion. The existing BiOCl/UiO-66 composite materials have limited photocatalytic active sites and poor electron transport performance.
By introducing Ce metal nodes into UiO-66 (Zr), forming a UiO-66 (Zr/Ce) support, and growing BiOCl nanosheets in situ on its surface, building a BiOCl/UiO-66 (Zr/Ce) heterojunction to regulate the interface properties to enhance the photocatalytic efficiency.
The high-efficiency photocatalytic oxidation performance of BiOCl/UiO-66 (Zr/Ce) heterojunction is achieved, and the capture ability and degradation efficiency of tetracycline are improved, reaching more than 91%.
Smart Images

Figure CN119500271A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of photocatalysis, and in particular relates to a BiOCl / UiO-66 (Zr / Ce) heterojunction photocatalyst and a preparation method and application thereof. Background Art
[0002] Organic pollutants in the water environment are diverse, complex in structure, and highly toxic. In particular, antibiotics discharged from wastewater in the pharmaceutical industry pose a serious threat to the surrounding ecosystem and human health. Therefore, finding new and effective methods to remove antibiotics is crucial to achieving sustainable development.
[0003] Photocatalytic technology is an efficient, green and environmentally friendly technology that can non-selectively oxidize a variety of organic pollutants and remove antibiotics under a wide range of conditions. As a common photocatalyst, the photocatalytic activity of BiOCl comes from its alternating [Bi2O2] 2+ With [Cl] - Layered structure, bismuth oxychloride is referred to as BiOCl in English, especially [Bi2O2] 2+ and [X] - The interlayer structure promotes the polarization of atomic orbitals, induces the generation of built-in electric fields, and is conducive to the separation and migration of photogenerated carriers, making its photocatalytic activity even better than materials such as TiO2. However, BiOCl has certain limitations: first, the wider band gap leads to insufficient visible light capture ability; second, the migration efficiency of photoinduced carriers is low and the recombination speed is too fast; in addition, photocorrosion will also affect its structural stability.
[0004] The construction of various BiOCl / MOF composite heterojunction materials has been widely studied as a method to modify BiOCl to improve the visible light light harvesting efficiency of BiOCl and overcome the problem of high carrier recombination rate of BiOCl. Among them, UiO-66 has better environmental tolerance including hydrothermal, mechanical and chemical stability and excellent hydrophilicity compared with other MOFs. Therefore, UiO-66 can be directly used as a photocatalyst in photocatalytic degradation reactions. However, due to the π-π electron transition of the aromatic ring in H2BDC, UiO-66 has poor absorption capacity for visible light. In addition, the existing preparation methods often make it difficult to control the uniform distribution of BiOCl on UiO-66, resulting in limited photocatalytic active sites and poor electron transport performance, resulting in poor photocatalytic effect. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a BiOCl / UiO-66 (Zr / Ce) heterojunction photocatalyst and its preparation method and application. The present invention introduces a new metal node Ce into UiO-66 (Zr) and utilizes the electron transfer between different metals to effectively reduce the band gap of a single BiOCl material, thereby improving the charge separation efficiency. In addition, BiOCl is constructed on UiO-66 (Zr / Ce) to form a heterojunction, and the interface properties of the BiOCl / UiO-66 (Zr / Ce) heterojunction are regulated by the doped metal Ce, thereby enhancing the interface electric field of the BiOCl / UiO-66 (Zr / Ce) heterojunction, and promoting the effective separation of photogenerated carriers under the action of the electric field. The synergistic effect of the heterojunction formed by UiO-66 (Zr / Ce) and BiOCl is used to enhance the light absorption capacity of the UiO-66 (Zr / Ce)-BiOCl composite material, provide sufficient active sites and electron transport performance, and thus improve the photocatalytic efficiency of the BiOCl / UiO-66 (Zr / Ce) heterojunction. The BiOCl / UiO-66 (Zr / Ce) heterojunction of the present invention has a suitable band gap and conduction band position, can generate a strong interface electric field, promote interface carrier separation efficiency, and has excellent photocatalytic oxidation performance.
[0006] The first object of the present invention is to provide a method for preparing a BiOCl / UiO-66 (Zr / Ce) heterojunction photocatalyst, comprising the following steps:
[0007] Step 1, preparation of UiO-66 (Zr / Ce): using UiO-66 (Zr) as a matrix, adopting a solvothermal method, partially doping the Zr position in the UiO-66 (Zr) with a metal node Ce to obtain UiO-66 (Zr / Ce).
[0008] It should be noted that the specific preparation process of UiO-66 (Zr / Ce) of the present invention is: terephthalic acid, soluble cerium salt, soluble zirconium salt and acid are added to the solvent in sequence, fully stirred and dissolved to obtain UiO-66 (Zr / Ce) precursor, and UiO-66 (Zr / Ce) is prepared by solvent thermal reaction. Since soluble zirconium salts are prone to hydrolysis and precipitation, the number of zirconium ions in the soluble zirconium salts is affected, and then the number of node metals in the UiO-66 (Zr / Ce) carrier is affected, and the coupling effect between the UiO-66 (Zr / Ce) carrier and BiOCl is further weakened. Therefore, the present invention enhances the solubility of soluble cerium salts and soluble zirconium salts in the solvent by adding a certain concentration of acid, and on the other hand, by adjusting the pH reaction conditions of the system, the appropriate acidity inhibits the hydrolysis of the zirconium salt and prevents the generation of by-products in the system. In addition, the addition of acid will not cause a significant change in the structure of the UiO-66 (Zr / Ce) carrier. The preferred acid of the present invention is concentrated formic acid or concentrated hydrochloric acid, and the volume ratio of the acid to the solvent is 1:3 to 4. In order to fully dissolve each component in the solvent, the preferred stirring temperature of the present invention is 20°C to 25°C, and the stirring time is 10s to 60s.
[0009] Different concentrations of cerium ions and zirconium ions will affect the number of node metals in the UiO-66 (Zr / Ce) carrier, thereby affecting the coupling effect between UiO-66 (Zr / Ce) and BiOCl. The present invention explores the effect of different amounts of soluble cerium salts, soluble zirconium salts and terephthalic acid on the number of node cerium metals and zirconium metals in the system, and finds that the UiO-66 (Zr / Ce) structure formed under this ratio is relatively stable and is a 3D structure. Preferably, the molar ratio of the soluble cerium salt, the soluble zirconium salt and terephthalic acid is 1:2:3-4, and the amount ratio of terephthalic acid to solvent is 1 mol:3mL-4mL.
[0010] Preferably, the soluble cerium salt is one of ammonium cerium nitrate and cerium chloride, which is used to provide the node metal in the UiO-66 (Zr / Ce) carrier.
[0011] Preferably, the soluble zirconium salt is one of zirconium oxynitrate and zirconium chloride, which is used to provide the node metal in the UiO-66 (Zr / Ce) carrier.
[0012] Preferably, the solvent is N,N-dimethylformamide, which is a non-protonic polar solvent. The positively charged end of the molecule is surrounded by methyl groups, forming a spatial barrier that prevents negative ions from approaching, thereby enhancing the activity of the negative ions and making the zirconium ions and cerium ions in the UiO-66 (Zr / Ce) precursor more soluble.
[0013] The temperature of the solvothermal reaction plays an important role in the formation of the UiO-66 (Zr / Ce) carrier structure. The preferred solvothermal reaction temperature of the present invention is 100° C. to 110° C., and the reaction time is 15 min to 20 min.
[0014] Step 2, prepare BiOCl / UiO-66 (Zr / Ce) heterojunction: take UiO-66 (Zr / Ce) as carrier, dissolve UiO-66 (Zr / Ce) and bismuth source and chlorine source in mannitol solution, make hydroxyl group in mannitol molecule react with bismuth ions provided by bismuth source and chloride ions provided by chlorine source through hydrothermal reaction, and in situ grow BiOCl nanosheets on the surface of UiO-66 (Zr / Ce), and obtain BiOCl / UiO-66 (Zr / Ce) heterojunction photocatalyst formed by composite of UiO-66 (Zr / Ce) and BiOCl nanosheets.
[0015] It should be noted that, by adding mannitol, the present invention can prevent the bismuth ions in the bismuth source from being oxidized in the mixed solution, and further prevent them from being hydrolyzed in the mixed solution. On the other hand, the hydroxyl groups in the mannitol molecules are used to form a coordination effect with the bismuth ions, thereby reducing the agglomeration of the bismuth ions in the mixed solution, and forming BiOCl nanocrystals with better dispersibility through a hydrothermal reaction. The mannitol solution of the present invention is obtained by dissolving mannitol in deionized water, and the preferred molar ratio of mannitol in the bismuth source and the mannitol solution is 1:2-3. The present invention provides the chloride ions required for forming the BiOCl structure by adding a saturated sodium chloride solution. The use of other chloride ion solutions may bring about other reactions. The preferred chloride source of the present invention is a sodium chloride solution, and the molar ratio of mannitol in the chloride source and the mannitol solution is 1:0.6-1.
[0016] The specific preparation process of the mixed solution of the present invention is: dissolving mannitol in deionized water to obtain a mannitol solution, dissolving UiO-66 (Zr / Ce) and bismuth salt in the mannitol solution in sequence, forming a suspension under ultrasound, and then adding a saturated sodium chloride solution to the suspension, stirring for 60 minutes, to obtain a mixed solution. Preferably, the mass fraction of the mannitol solution is 18.2wt%, and the ultrasound time is 30min to 40min.
[0017] Preferably, the mass ratio of the bismuth salt to UiO-66 (Zr / Ce) is 1-2:1.6-9.6.
[0018] Effect of hydrothermal reaction temperature and time on the formation of BiOCl / UiO-66 (Zr / Ce) heterojunction. The preferred hydrothermal reaction temperature of the present invention is 120°C to 180°C, and the reaction time is 2h to 4h.
[0019] The second object of the present invention is to provide a BiOCl / UiO-66 (Zr / Ce) heterojunction photocatalyst prepared by the above preparation method.
[0020] The third object of the present invention is to provide the use of the BiOCl / UiO-66 (Zr / Ce) heterojunction photocatalyst prepared by the above preparation method in the photocatalytic degradation of tetracycline hydrochloride in water.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The present invention uses UiO-66 (Zr) as a matrix and adopts a solvothermal method to partially dope the Zr position of the UiO-66 (Zr) with a metal node Ce to obtain UiO-66 (Zr / Ce). Since the doping of Ce atoms introduces new d orbital electronic states, these d orbitals hybridize with the original band structure of UiO-66 (Zr), thereby causing the band structure to be rearranged and forming a BiOCl / UiO-66 (Zr / Ce) heterojunction with BiOCl. The band gap width of BiOCl is significantly reduced, and the problem of BiOCl's weak response ability under visible light is improved; in addition, the increase of the metal node Ce, the effective charge transfer between Zr and Ce cations, and the Ce 3+ / Ce 4+ The formation of cyclic pairs realizes the accumulation of photogenerated electrons and holes in the interface microenvironment area, optimizes the microenvironment and local electronic structure of the BiOCl / UiO-66(Zr / Ce) heterojunction interface, and further enhances the capture ability of the BiOCl / UiO-66(Zr / Ce) heterojunction for tetracycline, making the tetracycline removal efficiency of the BiOCl / UiO-66(Zr / Ce) heterojunction composite material reach more than 91% under simulated visible light irradiation conditions.
[0023] The present invention uses UiO-66 (Zr / Ce) as a carrier, in-situ grows BiOCl on the surface of UiO-66 (Zr / Ce), and effectively constructs a BiOCl / UiO-66 (Zr / Ce) heterojunction. The present invention uses UiO-66 (Zr / Ce) as a carrier, dissolves UiO-66 (Zr / Ce) and a bismuth source and a chlorine source in a mannitol solution, and through a hydrothermal reaction, reacts the hydroxyl groups in the mannitol molecules with the bismuth ions provided by the bismuth source and the chlorine ions provided by the chlorine source, and in-situ grows BiOCl nanosheets on the surface of UiO-66 (Zr / Ce), thereby obtaining a BiOCl / UiO-66 (Zr / Ce) heterojunction photocatalyst formed by a composite of UiO-66 (Zr / Ce) and BiOCl nanosheets. The present invention confirms that different work functions are generated between BiOCl and UiO-66 (Zr / Ce) through energy band calculation and KPFM spectrum analysis. The combination of the two generates a strong interfacial electric field, which promotes the effective separation of photogenerated carriers and thus improves the photocatalytic efficiency.
[0024] The present invention adopts a simple hydrothermal synthesis method to prepare the BiOCl / UiO-66 (Zr / Ce) heterojunction photocatalyst, the preparation process is simple, green and pollution-free, the hydrothermal method is adopted for preparation, the operation is easy, the raw materials are cheap and readily available, and the catalyst is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 1 and 2. The XRD diagrams of 0.2BZC in Example 1 of the present invention, BiOCl in Comparative Example 1, UiO-66(Zr) in Comparative Example 2, UiO-66(Zr / Ce) in Comparative Example 3, and 0.2BZ in Comparative Example 4.
[0026] Figure 2 FT-IR spectra of 0.2BZC in Example 1 of the present invention, BiOCl in Comparative Example 1, UiO-66(Zr) in Comparative Example 2, UiO-66(Zr / Ce) in Comparative Example 3, and 0.2BZ in Comparative Example 4.
[0027] Figure 3 These are high-resolution transmission electron micrographs of 0.2BZC in Example 1 of the present invention, BiOCl in Comparative Example 1, and UiO-66 (Zr / Ce) in Comparative Example 3, wherein Figure (a) is BiOCl in Comparative Example 1, Figure (b) is UiO-66 (Zr / Ce) in Comparative Example 3, and Figure (c) is 0.2BZC in Example 1.
[0028] Figure 4 It is the UV-visible diffuse reflectance spectra of 0.2BZC in Example 1 of the present invention, BiOCl in Comparative Example 1, UiO-66(Zr) in Comparative Example 2, and UiO-66(Zr / Ce) in Comparative Example 3.
[0029] Figure 5 The photoluminescence spectra of 0.2BZC in Example 1 of the present invention, BiOCl in Comparative Example 1, and UiO-66 (Zr / Ce) in Comparative Example 3 are shown.
[0030] Figure 6 These are CPD diagrams of BiOCl in Comparative Example 1 and UiO-66 (Zr / Ce) in Comparative Example 3 of the present invention, wherein Figure (a) is BiOCl in Comparative Example 1 and Figure (b) is UiO-66 (Zr / Ce) in Comparative Example 3.
[0031] Figure 7 This is a visible light degradation efficiency diagram of tetracycline hydrochloride of 0.2BZC in Example 1 of the present invention, BiOCl in Comparative Example 1, UiO-66(Zr) in Comparative Example 2, UiO-66(Zr / Ce) in Comparative Example 3, and 0.2BZ in Comparative Example 4.
[0032] Figure 8 This is a graph showing the efficiency of visible light degradation of tetracycline hydrochloride by 0.2BZC in Example 1, 0.15BZC in Example 2, and 0.3BZC in Example 3 of the present invention.
[0033] Fig. 9 This is a graph showing the efficiency of tetracycline hydrochloride degradation by visible light of 0.2BZC in Example 1, 120-BZC in Example 4, and 180-BZC in Example 5 of the present invention.
[0034] Fig.10 This is a graph showing the efficiency of visible light degradation of tetracycline hydrochloride by 0.2BZC in Example 1, 2-BZC in Example 6, and 4-BZC in Example 7 of the present invention. DETAILED DESCRIPTION
[0035] In order to enable those skilled in the art to better understand that the technical solution of the present invention can be implemented, the present invention is further described below in conjunction with specific embodiments and drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] In the description of the present invention, unless otherwise specified, all reagents used are commercially available and all methods used are conventional techniques in the art.
[0037] The invention is further described below through specific examples.
[0038] Example 1
[0039] This embodiment provides a method for preparing a BiOCl / UiO-66 (Zr / Ce) heterojunction photocatalyst
[0040] Step 1, preparation of UiO-66 (Zr / Ce): using UiO-66 (Zr) as a matrix, adopting a solvothermal method, partially doping the Zr position in the UiO-66 (Zr) with a metal node Ce to obtain UiO-66 (Zr / Ce).
[0041] 1.1) Weigh 117 mg of ammonium cerium nitrate and dissolve it in 0.4 mL of deionized water to obtain an aqueous solution of ammonium cerium nitrate.
[0042] 1.2) Weigh 99 mg of zirconium oxynitrate solution into 0.8 mL of deionized water to obtain a zirconium oxynitrate aqueous solution.
[0043] 1.3) 139 mg of terephthalic acid, 0.4 mL of cerium ammonium nitrate aqueous solution, 0.8 mL of zirconium oxynitrate aqueous solution and 1.03 mL of concentrated formic acid (HCOOH, 100%) were successively dissolved in 3.6 mL of N,N-dimethylformamide under stirring to obtain a UiO-66 (Zr / Ce) precursor.
[0044] 1.4) The UiO-66 (Zr / Ce) precursor was transferred to a single-mouth eggplant-shaped bottle and sealed, reacted at 100 ° C for 15 minutes, cooled naturally to room temperature, and then centrifuged and washed with deionized water and anhydrous ethanol, and then transferred to a 60 ° C oven for drying for 12 hours to obtain UiO-66 (Zr / Ce).
[0045] Step 2, prepare BiOCl / UiO-66 (Zr / Ce) heterojunction: take UiO-66 (Zr / Ce) as carrier, dissolve UiO-66 (Zr / Ce) and bismuth source and chlorine source in mannitol solution, make hydroxyl group in mannitol molecule react with bismuth ions provided by bismuth source and chloride ions provided by chlorine source through hydrothermal reaction, and in situ grow BiOCl nanosheets on the surface of UiO-66 (Zr / Ce), and obtain BiOCl / UiO-66 (Zr / Ce) heterojunction photocatalyst formed by composite of UiO-66 (Zr / Ce) and BiOCl nanosheets.
[0046] 2.1) Weigh 0.455 g of mannitol and dissolve it in 25 mL of deionized water to obtain a mannitol solution.
[0047] 2.2) Weigh 0.485 g of Bi(NO3)3·5H2O and 0.2 g of UiO-66(Zr / Ce) obtained in step 1 above, dissolve them in 25 mL of mannitol solution, ultrasonicate for 0.5 h, then add 5 mL of saturated sodium chloride solution, stir for 1 h, and obtain a mixed solution.
[0048] 2.3) The mixed solution was transferred into a 50 ml hydrothermal reactor, reacted at 160 ° C for 3 h, cooled naturally to room temperature, and then centrifuged and washed with deionized water and anhydrous ethanol. It was then transferred to a 60 ° C oven and dried for 12 h to obtain a BiOCl / UiO-66 (Zr / Ce) heterojunction, which was named 0.2BZC.
[0049] Example 2
[0050] This embodiment provides a method for preparing a BiOCl / UiO-66 (Zr / Ce) heterojunction photocatalyst
[0051] Step 1, preparation of UiO-66 (Zr / Ce): using UiO-66 (Zr) as a matrix, adopting a solvothermal method, partially doping the Zr position in the UiO-66 (Zr) with a metal node Ce to obtain UiO-66 (Zr / Ce).
[0052] 1.1) Weigh 117 mg of ammonium cerium nitrate and dissolve it in 0.4 mL of deionized water to obtain an aqueous solution of ammonium cerium nitrate.
[0053] 1.2) Weigh 99 mg of zirconium oxynitrate solution into 0.8 mL of deionized water to obtain a zirconium oxynitrate aqueous solution.
[0054] 1.3) 139 mg of terephthalic acid, 0.4 mL of cerium ammonium nitrate aqueous solution, 0.8 mL of zirconium oxynitrate aqueous solution and 1.03 mL of concentrated formic acid (HCOOH, 100%) were successively dissolved in 3.6 mL of N,N-dimethylformamide under stirring to obtain a UiO-66 (Zr / Ce) precursor.
[0055] 1.4) The UiO-66 (Zr / Ce) precursor was transferred to a single-mouth eggplant-shaped bottle and sealed, reacted at 100 ° C for 15 minutes, cooled naturally to room temperature, and then centrifuged and washed with deionized water and anhydrous ethanol, and then transferred to a 60 ° C oven for drying for 12 hours to obtain UiO-66 (Zr / Ce).
[0056] Step 2, prepare BiOCl / UiO-66 (Zr / Ce) heterojunction: take UiO-66 (Zr / Ce) as carrier, dissolve UiO-66 (Zr / Ce) and bismuth source and chlorine source in mannitol solution, make hydroxyl group in mannitol molecule react with bismuth ions provided by bismuth source and chloride ions provided by chlorine source through hydrothermal reaction, and in situ grow BiOCl nanosheets on the surface of UiO-66 (Zr / Ce), and obtain BiOCl / UiO-66 (Zr / Ce) heterojunction photocatalyst formed by composite of UiO-66 (Zr / Ce) and BiOCl nanosheets.
[0057] 2.1) Weigh 0.455 g of mannitol and dissolve it in 25 mL of deionized water to obtain a mannitol solution.
[0058] 2.2) Weigh 0.485 g of Bi(NO3)3·5H2O and 0.15 g of UiO-66(Zr / Ce) obtained in step 1 above, dissolve them in 25 mL of mannitol solution, ultrasonicate for 0.5 h, then add 5 mL of saturated sodium chloride solution, stir for 1 h, and obtain a mixed solution.
[0059] 2.3) The mixed solution was transferred into a 50 ml hydrothermal reactor, reacted at 160 ° C for 3 h, cooled naturally to room temperature, and then centrifuged and washed with deionized water and anhydrous ethanol. It was then transferred to a 60 ° C oven and dried for 12 h to obtain a BiOCl / UiO-66 (Zr / Ce) heterojunction, which was named 0.15BZC.
[0060] The difference between Example 2 and Example 1 is that in Example 2, the mass ratio of Bi(NO3)3·5H2O and UiO-66(Zr / Ce) is controlled to be 0.485:0.15.
[0061] Example 3
[0062] This embodiment provides a method for preparing a BiOCl / UiO-66 (Zr / Ce) heterojunction photocatalyst
[0063] Step 1, preparation of UiO-66 (Zr / Ce): using UiO-66 (Zr) as a matrix, adopting a solvothermal method, partially doping the Zr position in the UiO-66 (Zr) with a metal node Ce to obtain UiO-66 (Zr / Ce).
[0064] 1.1) Weigh 117 mg of ammonium cerium nitrate and dissolve it in 0.4 mL of deionized water to obtain an aqueous solution of ammonium cerium nitrate.
[0065] 1.2) Weigh 99 mg of zirconium oxynitrate solution into 0.8 mL of deionized water to obtain a zirconium oxynitrate aqueous solution.
[0066] 1.3) 139 mg of terephthalic acid, 0.4 mL of cerium ammonium nitrate aqueous solution, 0.8 mL of zirconium oxynitrate aqueous solution and 1.03 mL of concentrated formic acid (HCOOH, 100%) were successively dissolved in 3.6 mL of N,N-dimethylformamide under stirring to obtain a UiO-66 (Zr / Ce) precursor.
[0067] 1.4) The UiO-66 (Zr / Ce) precursor was transferred to a single-mouth eggplant-shaped bottle and sealed, reacted at 100 ° C for 15 minutes, cooled naturally to room temperature, and then centrifuged and washed with deionized water and anhydrous ethanol, and then transferred to a 60 ° C oven for drying for 12 hours to obtain UiO-66 (Zr / Ce).
[0068] Step 2, prepare BiOCl / UiO-66 (Zr / Ce) heterojunction: take UiO-66 (Zr / Ce) as carrier, dissolve UiO-66 (Zr / Ce) and bismuth source and chlorine source in mannitol solution, make hydroxyl group in mannitol molecule react with bismuth ions provided by bismuth source and chloride ions provided by chlorine source through hydrothermal reaction, and in situ grow BiOCl nanosheets on the surface of UiO-66 (Zr / Ce), and obtain BiOCl / UiO-66 (Zr / Ce) heterojunction photocatalyst formed by composite of UiO-66 (Zr / Ce) and BiOCl nanosheets.
[0069] 2.1) Weigh 0.455 g of mannitol and dissolve it in 25 mL of deionized water to obtain a mannitol solution.
[0070] 2.2) Weigh 0.485 g of Bi(NO3)3·5H2O and 0.3 g of UiO-66(Zr / Ce) obtained in step 1 above, dissolve them in 25 mL of mannitol solution, ultrasonicate for 0.5 h, then add 5 mL of saturated sodium chloride solution, stir for 1 h, and obtain a mixed solution.
[0071] 2.3) The mixed solution was transferred into a 50 ml hydrothermal reactor, reacted at 160 ° C for 3 h, cooled naturally to room temperature, and then washed by centrifugation with deionized water and anhydrous ethanol, and then transferred to a 60 ° C oven for drying for 12 h to obtain a BiOCl / UiO-66 (Zr / Ce) heterojunction, which was named 0.3BZC.
[0072] The difference between Example 3 and Example 1 is that in Example 3, the mass ratio of Bi(NO3)3·5H2O and UiO-66(Zr / Ce) is controlled to be 0.485:0.3.
[0073] Example 4
[0074] This embodiment provides a method for preparing a BiOCl / UiO-66 (Zr / Ce) heterojunction photocatalyst
[0075] Step 1, preparation of UiO-66 (Zr / Ce): using UiO-66 (Zr) as a matrix, adopting a solvothermal method, partially doping the Zr position in the UiO-66 (Zr) with a metal node Ce to obtain UiO-66 (Zr / Ce).
[0076] 1.1) Weigh 117 mg of ammonium cerium nitrate and dissolve it in 0.4 mL of deionized water to obtain an aqueous solution of ammonium cerium nitrate.
[0077] 1.2) Weigh 99 mg of zirconium oxynitrate solution into 0.8 mL of deionized water to obtain a zirconium oxynitrate aqueous solution.
[0078] 1.3) 139 mg of terephthalic acid, 0.4 mL of cerium ammonium nitrate aqueous solution, 0.8 mL of zirconium oxynitrate aqueous solution and 1.03 mL of concentrated formic acid (HCOOH, 100%) were successively dissolved in 4.0 mL of N,N-dimethylformamide under stirring to obtain a UiO-66 (Zr / Ce) precursor.
[0079] 1.4) The UiO-66 (Zr / Ce) precursor was transferred to a single-mouth eggplant-shaped bottle and sealed, reacted at 100 ° C for 15 minutes, cooled naturally to room temperature, and then centrifuged and washed with deionized water and anhydrous ethanol, and then transferred to a 60 ° C oven for drying for 12 hours to obtain UiO-66 (Zr / Ce).
[0080] Step 2, prepare BiOCl / UiO-66 (Zr / Ce) heterojunction: take UiO-66 (Zr / Ce) as carrier, dissolve UiO-66 (Zr / Ce) and bismuth source and chlorine source in mannitol solution, make hydroxyl group in mannitol molecule react with bismuth ions provided by bismuth source and chloride ions provided by chlorine source through hydrothermal reaction, and in situ grow BiOCl nanosheets on the surface of UiO-66 (Zr / Ce), and obtain BiOCl / UiO-66 (Zr / Ce) heterojunction photocatalyst formed by composite of UiO-66 (Zr / Ce) and BiOCl nanosheets.
[0081] 2.1) Weigh 0.455 g of mannitol and dissolve it in 25 mL of deionized water to obtain a mannitol solution.
[0082] 2.2) Weigh 0.485 g of Bi(NO3)3·5H2O and 0.05 g of UiO-66(Zr / Ce) obtained in step 1 above, dissolve them in 25 mL of mannitol solution, sonicate for 0.5 h, then add 5 mL of saturated sodium chloride solution, stir for 1 h, and obtain a mixed solution.
[0083] 2.3) The mixed solution was transferred into a 50 ml hydrothermal reactor and reacted at 120 °C for 3 h. After cooling naturally to room temperature, it was washed by centrifugation with deionized water and anhydrous ethanol, and then transferred to a 60 °C oven for drying for 12 h to obtain a BiOCl / UiO-66 (Zr / Ce) heterojunction, which was named 120BZC.
[0084] The difference between Example 4 and Example 1 is that the hydrothermal reaction temperature of Example 4 is 120°C.
[0085] Example 5
[0086] This embodiment provides a method for preparing a BiOCl / UiO-66 (Zr / Ce) heterojunction photocatalyst
[0087] Step 1, preparation of UiO-66 (Zr / Ce): using UiO-66 (Zr) as a matrix, adopting a solvothermal method, partially doping the Zr position in the UiO-66 (Zr) with a metal node Ce to obtain UiO-66 (Zr / Ce).
[0088] 1.1) Weigh 117 mg of ammonium cerium nitrate and dissolve it in 0.4 mL of deionized water to obtain an aqueous solution of ammonium cerium nitrate.
[0089] 1.2) Weigh 99 mg of zirconium oxynitrate solution into 0.8 mL of deionized water to obtain a zirconium oxynitrate aqueous solution.
[0090] 1.3) 139 mg of terephthalic acid, 0.4 mL of cerium ammonium nitrate aqueous solution, 0.8 mL of zirconium oxynitrate aqueous solution and 1.03 mL of concentrated formic acid (HCOOH, 100%) were successively dissolved in 3.0 mL of N,N-dimethylformamide under stirring to obtain a UiO-66 (Zr / Ce) precursor.
[0091] 1.4) The UiO-66 (Zr / Ce) precursor was transferred to a single-mouth eggplant-shaped bottle and sealed, reacted at 100 ° C for 15 minutes, cooled naturally to room temperature, and then centrifuged and washed with deionized water and anhydrous ethanol, and then transferred to a 60 ° C oven for drying for 12 hours to obtain UiO-66 (Zr / Ce).
[0092] Step 2, prepare BiOCl / UiO-66 (Zr / Ce) heterojunction: take UiO-66 (Zr / Ce) as carrier, dissolve UiO-66 (Zr / Ce) and bismuth source and chlorine source in mannitol solution, make hydroxyl group in mannitol molecule react with bismuth ions provided by bismuth source and chloride ions provided by chlorine source through hydrothermal reaction, and in situ grow BiOCl nanosheets on the surface of UiO-66 (Zr / Ce), and obtain BiOCl / UiO-66 (Zr / Ce) heterojunction photocatalyst formed by composite of UiO-66 (Zr / Ce) and BiOCl nanosheets.
[0093] 2.1) Weigh 0.364 g of mannitol and dissolve it in 25 mL of deionized water to obtain a mannitol solution.
[0094] 2.2) Weigh 0.485 g of Bi(NO3)3·5H2O and 0.2 g of UiO-66(Zr / Ce) obtained in step 1 above, dissolve them in 25 mL of mannitol solution, ultrasonicate for 0.5 h, then add 5 mL of saturated sodium chloride solution, stir for 1 h, and obtain a mixed solution.
[0095] 2.3) The mixed solution was transferred into a 50 ml hydrothermal reactor, reacted at 180 ° C for 3 h, cooled naturally to room temperature, and then centrifuged and washed with deionized water and anhydrous ethanol. It was then transferred to a 60 ° C oven and dried for 12 h to obtain a BiOCl / UiO-66 (Zr / Ce) heterojunction, which was named 180BZC.
[0096] The difference between Example 5 and Example 1 is that the hydrothermal reaction temperature of Example 5 is 180°C.
[0097] Example 6
[0098] This embodiment provides a method for preparing a BiOCl / UiO-66 (Zr / Ce) heterojunction photocatalyst
[0099] Step 1, preparation of UiO-66 (Zr / Ce): using UiO-66 (Zr) as a matrix, adopting a solvothermal method, partially doping the Zr position in the UiO-66 (Zr) with a metal node Ce to obtain UiO-66 (Zr / Ce).
[0100] 1.1) Weigh 117 mg of ammonium cerium nitrate and dissolve it in 0.4 mL of deionized water to obtain an aqueous solution of ammonium cerium nitrate.
[0101] 1.2) Take 99 mg of zirconium oxynitrate solution and add it to 0.8 mL of deionized water to obtain a zirconium oxynitrate aqueous solution.
[0102] 1.3) 139 mg of terephthalic acid, 0.4 mL of cerium ammonium nitrate aqueous solution, 0.8 mL of zirconium oxynitrate aqueous solution and 1.03 mL of concentrated formic acid (HCOOH, 100%) were successively dissolved in 3.6 mL of N,N-dimethylformamide under stirring to obtain a UiO-66 (Zr / Ce) precursor.
[0103] 1.4) The UiO-66 (Zr / Ce) precursor was transferred to a single-mouth eggplant-shaped bottle and sealed, reacted at 100 ° C for 15 minutes, cooled naturally to room temperature, and then centrifuged and washed with deionized water and anhydrous ethanol, and then transferred to a 60 ° C oven for drying for 12 hours to obtain UiO-66 (Zr / Ce).
[0104] Step 2, prepare BiOCl / UiO-66 (Zr / Ce) heterojunction: take UiO-66 (Zr / Ce) as carrier, dissolve UiO-66 (Zr / Ce) and bismuth source and chlorine source in mannitol solution, make hydroxyl group in mannitol molecule react with bismuth ions provided by bismuth source and chloride ions provided by chlorine source through hydrothermal reaction, and in situ grow BiOCl nanosheets on the surface of UiO-66 (Zr / Ce), and obtain BiOCl / UiO-66 (Zr / Ce) heterojunction photocatalyst formed by composite of UiO-66 (Zr / Ce) and BiOCl nanosheets.
[0105] 2.1) Weigh 0.546 g of mannitol and dissolve it in 25 mL of deionized water to obtain a mannitol solution.
[0106] 2.2) Weigh 0.485 g of Bi(NO3)3·5H2O and 0.2 g of UiO-66(Zr / Ce) obtained in step 1 above, dissolve them in 25 mL of mannitol solution, ultrasonicate for 0.5 h, then add 5 mL of saturated sodium chloride solution, stir for 1 h, and obtain a mixed solution.
[0107] 2.3) The mixed solution was transferred into a 50 ml hydrothermal reactor, reacted at 160 ° C for 2 h, cooled naturally to room temperature, and then centrifuged and washed with deionized water and anhydrous ethanol. It was then transferred to a 60 ° C oven and dried for 12 h to obtain a BiOCl / UiO-66 (Zr / Ce) heterojunction, which was named 2BZC.
[0108] The difference between Example 6 and Example 1 is that the hydrothermal reaction time of Example 6 is 2 hours.
[0109] Example 7
[0110] This embodiment provides a method for preparing a BiOCl / UiO-66 (Zr / Ce) heterojunction photocatalyst
[0111] Step 1, preparation of UiO-66 (Zr / Ce): using UiO-66 (Zr) as a matrix, adopting a solvothermal method, partially doping the Zr position in the UiO-66 (Zr) with a metal node Ce to obtain UiO-66 (Zr / Ce).
[0112] 1.1) Weigh 117 mg of ammonium cerium nitrate and dissolve it in 0.4 mL of deionized water to obtain an aqueous solution of ammonium cerium nitrate.
[0113] 1.2) Weigh 99 mg of zirconium oxynitrate solution into 0.8 mL of deionized water to obtain a zirconium oxynitrate aqueous solution.
[0114] 1.3) 139 mg of terephthalic acid, 0.4 mL of cerium ammonium nitrate aqueous solution, 0.8 mL of zirconium oxynitrate aqueous solution and 1.03 mL of concentrated formic acid (HCOOH, 100%) were successively dissolved in 3.6 mL of N,N-dimethylformamide under stirring to obtain a UiO-66 (Zr / Ce) precursor.
[0115] 1.4) The UiO-66 (Zr / Ce) precursor was transferred to a single-mouth eggplant-shaped bottle and sealed, reacted at 100 ° C for 15 minutes, cooled naturally to room temperature, and then centrifuged and washed with deionized water and anhydrous ethanol, and then transferred to a 60 ° C oven for drying for 12 hours to obtain UiO-66 (Zr / Ce).
[0116] Step 2, prepare BiOCl / UiO-66 (Zr / Ce) heterojunction: take UiO-66 (Zr / Ce) as carrier, dissolve UiO-66 (Zr / Ce) and bismuth source and chlorine source in mannitol solution, make hydroxyl group in mannitol molecule react with bismuth ions provided by bismuth source and chloride ions provided by chlorine source through hydrothermal reaction, and in situ grow BiOCl nanosheets on the surface of UiO-66 (Zr / Ce), and obtain BiOCl / UiO-66 (Zr / Ce) heterojunction photocatalyst formed by composite of UiO-66 (Zr / Ce) and BiOCl nanosheets.
[0117] 2.1) Weigh 0.455 g of mannitol and dissolve it in 25 mL of deionized water to obtain a mannitol solution.
[0118] 2.2) Weigh 0.485 g of Bi(NO3)3·5H2O and 0.2 g of UiO-66(Zr / Ce) obtained in step 1 above, dissolve them in 25 mL of mannitol solution, ultrasonicate for 0.5 h, then add 5 mL of saturated sodium chloride solution, stir for 1 h, and obtain a mixed solution.
[0119] 2.3) The mixed solution was transferred into a 50 ml hydrothermal reactor, reacted at 160 ° C for 4 h, cooled naturally to room temperature, and then centrifuged and washed with deionized water and anhydrous ethanol. It was then transferred to a 60 ° C oven and dried for 12 h to obtain a BiOCl / UiO-66 (Zr / Ce) heterojunction, which was named 4BZC.
[0120] The difference between Example 7 and Example 1 is that the hydrothermal reaction time of Example 7 is 4 hours.
[0121] Comparative Example 1
[0122] This comparative example provides a method for preparing BiOCl
[0123] 0.455 g of mannitol was weighed and dissolved in 25 mL of deionized water to obtain a mannitol solution; 0.485 g of Bi(NO3)3·5H2O was weighed and dissolved in 25 mL of mannitol solution, ultrasonicated for 0.5 h, then 5 mL of saturated sodium chloride solution was added, and stirring was continued for 1 h to obtain a mixed solution; the mixed solution was transferred into a 50 ml hydrothermal reactor, reacted at 160 ° C for 3 h, naturally cooled to room temperature, and then centrifuged and washed with deionized water and anhydrous ethanol, and then transferred to a 60 ° C oven for drying for 12 h to obtain BiOCl.
[0124] The difference between Comparative Example 1 and Example 1 is that under the same conditions and parameters, only BiOCl is prepared in Comparative Example 1.
[0125] Comparative Example 2
[0126] This comparative example provides a method for preparing UiO-66(Zr)
[0127] 0.466 g of zirconium chloride and 1 ml of HCl (36% to 38%) were added to 50 mL of N, N-dimethylformamide solution in sequence, and ultrasonicated for 5 min to obtain a mixed solution; then 0.382 g of terephthalic acid was added to the mixed solution, and stirring was continued at room temperature for 30 min to obtain a UiO-66 (Zr) solution, which was reacted at 130 ° C for 24 h, naturally cooled to room temperature, and then centrifuged and washed with deionized water and anhydrous ethanol, and then transferred to a 60 ° C oven for drying for 12 h to obtain UiO-66 (Zr).
[0128] The difference between Comparative Example 2 and Example 1 is that the soluble zirconium salt and the strong acid are changed to prepare UiO-66(Zr).
[0129] Comparative Example 3
[0130] This comparative example provides a method for preparing UiO-66 (Zr / Ce)
[0131] 117 mg of ammonium cerium nitrate was weighed and dissolved in 0.4 mL of deionized water to obtain an ammonium cerium nitrate aqueous solution; 99 mg of zirconium oxynitrate solution was weighed and dissolved in 0.8 mL of deionized water to obtain an aqueous zirconium oxynitrate solution; 139 mg of terephthalic acid, 0.4 mL of ammonium cerium nitrate aqueous solution, 0.8 mL of zirconium oxynitrate aqueous solution and 1.03 mL of concentrated formic acid (HCOOH, 100%) were successively dissolved in 3.6 mL of N, N-dimethylformamide under stirring to obtain a UiO-66 (Zr / Ce) precursor; the UiO-66 (Zr / Ce) precursor was transferred to a single-mouth eggplant-shaped bottle and sealed, reacted at 100° C. for 15 min, naturally cooled to room temperature, centrifuged and washed with deionized water and anhydrous ethanol, and then transferred to a 60° C. oven for drying for 12 h to obtain UiO-66 (Zr / Ce).
[0132] The difference between Comparative Example 3 and Example 1 is that under the same conditions and parameters, only UiO-66 (Zr / Ce) was prepared in Comparative Example 3.
[0133] Comparative Example 4
[0134] This comparative example provides a method for preparing a BiOCl / UiO-66(Zr) heterojunction
[0135] Step 1. Add 0.466 g of zirconium chloride and 1 ml of HCl (36%-38%) to 50 mL of N,N-dimethylformamide solution in sequence, and ultrasonicate for 5 minutes to obtain a mixed solution; then add 0.382 g of terephthalic acid to the mixed solution, and stir continuously for 30 minutes at room temperature to obtain a UiO-66 (Zr) solution, react at 130° C. for 24 hours, cool naturally to room temperature, and then centrifuge and wash with deionized water and anhydrous ethanol, and then transfer to a 60° C. oven and dry for 12 hours to obtain UiO-66 (Zr).
[0136] Step 2: Weigh 0.455g of mannitol and dissolve it in 25mL of deionized water to obtain a mannitol solution; weigh 0.485g of Bi(NO3)3·5H2O and 0.2g of UiO-66(Zr) and dissolve them in 25ml of mannitol solution, ultrasonicate for 0.5h, then add 5mL of saturated sodium chloride solution and stir for 1h to obtain a BiOCl / UiO-66(Zr) solution. Transfer the BiOCl / UiO-66(Zr) solution into a 50ml hydrothermal reactor, react at 160℃ for 2h, cool naturally to room temperature, centrifuge and wash with deionized water and anhydrous ethanol, then transfer to a 60℃ oven and dry for 12h to obtain a BiOCl / UiO-66(Zr) heterojunction, which is named 0.2BZ.
[0137] The difference between Comparative Example 4 and Example 1 is that the soluble zirconium salt and the strong acid are changed to prepare the BiOCl / UiO-66 (Zr) heterojunction.
[0138] Experimental Section
[0139] The present invention conducted the following structural characterization and performance tests on the samples prepared in the above-mentioned Examples 1 to 7 and Comparative Examples 1 to 4:
[0140] Figure 1 The XRD diagrams are shown for 0.2BZC in Example 1 of the present invention, BiOCl in Comparative Example 1, UiO-66(Zr) in Comparative Example 2, UiO-66(Zr / Ce) in Comparative Example 3, and 0.2BZ in Comparative Example 4. Figure 1It can be seen that strong diffraction peaks are observed at 2θ=25.808°, 32.462° and 33.391°, which correspond to the (101), (102) and (111) crystal planes of BiOCl prepared in Comparative Example 1, respectively. Characteristic peaks are observed at 7.35° and 8.5° for UiO-66(Zr) prepared in Comparative Example 3, which correspond to the (111) and (200) crystal planes. Compared with single BiOCl, two new diffraction peaks appear at 2θ=7.40° and 8.54° in Example 1 and Comparative Example 4, which are the (111) and (200) planes of UiO-66, which proves the successful formation of the BiOCl / UiO-66(Zr / Ce) heterostructure prepared by the present invention. Compared with the 0.2BZ prepared in Comparative Example 4, the C peak position of the 0.2BZ prepared in Example 1 shifts to the left, confirming that Ce doping may change the local chemical environment of the heterojunction interface and affect the interaction between the catalyst and the reactants.
[0141] Figure 2 FT-IR spectra of 0.2BZC in Example 1 of the present invention, BiOCl in Comparative Example 1, UiO-66(Zr) in Comparative Example 2, UiO-66(Zr / Ce) in Comparative Example 3, and 0.2BZ in Comparative Example 4. Figure 2 As can be seen, 1400cm - The peak at 1 is COO - Asymmetric stretching vibration peak, 1505cm - The peak at 1 is the C=C stretching vibration peak of the aromatic ring, indicating that except for BiOCl, the other samples all have aromatic structures, confirming that BiOCl and UiO-66 have formed a heterojunction structure; in addition, the addition of Ce will cause the metal oxygen bond to red-shift, causing the MO peak to shift from 548 cm - 1 point deviation 530cm - 1. The red shift phenomenon indicates that the introduction of Ce increases the electron cloud density of the metal oxygen bond, resulting in the accumulation of electrons at the interface, enhancing the interfacial electric field and promoting charge separation.
[0142] Figure 3 The high-resolution transmission electron micrographs of 0.2BZC in Example 1 of the present invention, BiOCl in Comparative Example 1, and UiO-66 (Zr / Ce) in Comparative Example 3 are shown in Figure (a) for BiOCl in Comparative Example 1, Figure (b) for UiO-66 (Zr / Ce) in Comparative Example 3, and Figure (c) for 0.2BZC in Example 1. Figure 3 From (a) in the figure, we can see that BiOCl presents a two-dimensional layered structure, with a size range of about 0.14-0.75um. Figure 3 In (b), it can be seen that UiO-66(Zr / Ce) presents a non-octahedral morphology. Figure 3In (c), there is a close interface between UiO-66(Zr / Ce) and BiOCl, indicating that the present invention successfully forms a heterojunction structure.
[0143] Figure 4 The UV-visible diffuse reflectance spectra of 0.2BZC in Example 1 of the present invention, BiOCl in Comparative Example 1, UiO-66(Zr) in Comparative Example 2, and UiO-66(Zr / Ce) in Comparative Example 3 are shown in FIG. Figure 4 It can be seen that UiO-66 shows negligible absorption in the visible light range. When the Ce element is introduced, the bimetallic UiO-66 (Zr / Ce) shows a significant enhancement in light absorption in the visible light region. Compared with pure BiOCl, the 0.2BZC heterojunction has an enhanced light absorption capacity, and the synergistic effect of BiOCl and UiO-66 (Zr / Ce) enhances the material's light absorption capacity, which helps to improve the photocatalytic efficiency.
[0144] Figure 5 The photoluminescence spectra of 0.2BZC in Example 1 of the present invention, BiOCl in Comparative Example 1, and UiO-66 (Zr / Ce) in Comparative Example 3. Compared with pure phase BiOCl and UiO-66 (Zr / Ce), the 0.2BZC heterojunction photocatalyst prepared in Example 1 has significantly reduced photogenerated electron-hole recombination rate and improved quantum utilization efficiency.
[0145] Figure 6 The CPD diagrams of BiOCl in Comparative Example 1 and UiO-66 (Zr / Ce) in Comparative Example 3 of the present invention are shown in Figure (a) for BiOCl in Comparative Example 1 and Figure (b) for UiO-66 (Zr / Ce) in Comparative Example 3. Figure 6 As shown in the figure, the CDP of BiOCl and UiO-66 (Zr / Ce) are -436mV and -323mV, respectively. Therefore, the corresponding work functions are calculated to be 3.81 and 3.93, respectively. That is, the Fermi level of BiOCl is -3.81vsVacuum, which is higher than the Fermi level of UiO-66 (Zr / Ce) -3.93vsVacuum. In the absence of light irradiation, once the two components are in contact, free electrons will be transferred from BiOCl to UiO-66 (Zr / Ce) until the two Fermi levels match, thereby forming an internal electric field at the BiOCl / UiO-66 (Zr / Ce) interface to promote the separation of photogenerated carriers. This shows that different work functions are generated between BiOCl and UiO-66 (Zr / Ce), and the combination of the two generates a strong interfacial electric field, which promotes the effective separation of photogenerated carriers and thus improves the photocatalytic efficiency.
[0146] Figure 7The figure is a graph showing the efficiency of tetracycline hydrochloride degradation by visible light of 0.2BZC in Example 1 of the present invention, BiOCl in Comparative Example 1, UiO-66(Zr) in Comparative Example 2, UiO-66(Zr / Ce) in Comparative Example 3 and 0.2BZ in Comparative Example 4. Figure 7 It can be seen that the degradation rate of tetracycline hydrochloride in 120 min by 0.2BZC prepared in Example 1 is 91%, and the degradation rates of TC in 120 min by BiOCl prepared in Comparative Example 1, UiO-66 (Zr) prepared in Comparative Example 2, UiO-66 (Zr / Ce) prepared in Comparative Example 3 and 0.2BZ prepared in Comparative Example 4 are 40%, 14%, 41% and 47%, respectively, indicating that the degradation rate of TC in 120 min by 0.2BZC prepared in Example 1 is much higher than that of single BiOCl, UiO-66 (Zr), UiO-66 (Zr / Ce) and 0.2BZ. This shows that the present invention uses UiO-66 (Zr) as a matrix, and partially dopes the Zr position in the UiO-66 (Zr) to introduce a metal node Ce, and the introduction of Ce and the synergistic effect of the heterojunction make 0.2BZC have a higher photocatalytic degradation performance.
[0147] Figure 8 The figure shows the efficiency of tetracycline hydrochloride degradation under visible light of 0.2BZC in Example 1, 0.15BZC in Example 2 and 0.3BZC in Example 3. The effects of different mass ratios of Bi(NO3)3·5H2O and UiO-66(Zr / Ce) on the composite photocatalyst are compared. With the increase of UiO-66(Zr / Ce) content, the degradation of tetracycline hydrochloride by the photocatalyst under visible light first increases and then decreases, indicating that the appropriate mass ratio of BiOCl to UiO-66(Zr / Ce) is very important for improving the photocatalytic activity of the catalyst.
[0148] Fig. 9 The figure is a diagram of the visible light degradation efficiency of tetracycline hydrochloride of 0.2BZC in Example 1, 120-BZC in Example 4, and 180-BZC in Example 5 of the present invention. The effects of different hydrothermal reaction temperatures on the catalytic degradation performance of 0.2BZC photocatalyst under visible light for tetracycline hydrochloride are compared. It can be seen that the degradation efficiency of 0.2BZC photocatalyst increases first and then decreases with the increase of hydrothermal reaction temperature. Therefore, the preferred hydrothermal reaction temperature of the present invention is 120°C to 180°C, and the more preferred hydrothermal reaction temperature is 160°C.
[0149] Fig.10The figure is a diagram of the efficiency of tetracycline hydrochloride degradation under visible light of 0.2BZC in Example 1, 2-BZC in Example 6 and 4-BZC in Example 7 of the present invention. The present invention compares the effects of different hydrothermal reaction times on the catalytic degradation of tetracycline hydrochloride by 0.2BZC photocatalyst under visible light, and it can be seen that the effect of hydrothermal reaction time on catalytic degradation is more significant. Therefore, the preferred hydrothermal reaction time of the present invention is 2h to 4h, and the more preferred hydrothermal reaction time is 3h.
[0150] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.
Claims
1. A method for preparing a BiOCl / UiO-66 (Zr / Ce) heterojunction photocatalyst, characterized in that: The following steps are involved: Using UiO-66(Zr) as a matrix, a solvothermal method is used to partially dope the Zr position of the UiO-66(Zr) with a metal node Ce to obtain UiO-66(Zr / Ce); Taking UiO-66(Zr / Ce) as the carrier, UiO-66(Zr / Ce), a bismuth source and a chlorine source were dissolved in a mannitol solution. Through a hydrothermal reaction, the hydroxyl groups in the mannitol molecules reacted with the bismuth ions provided by the bismuth source and the chloride ions provided by the chlorine source, and BiOCl nanosheets were in situ grown on the surface of UiO-66(Zr / Ce), thereby obtaining a BiOCl / UiO-66(Zr / Ce) heterojunction photocatalyst composed of UiO-66(Zr / Ce) and BiOCl nanosheets.
2. The method for preparing the BiOCl / UiO-66 (Zr / Ce) heterojunction photocatalyst according to claim 1, characterized in that: The mass ratio of the bismuth source to UiO-66 (Zr / Ce) is 1-2:1.6-9.
6.
3. The method for preparing the BiOCl / UiO-66 (Zr / Ce) heterojunction photocatalyst according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 120° C. to 180° C., and the time of the hydrothermal reaction is 2 h to 4 h.
4. The method for preparing the BiOCl / UiO-66 (Zr / Ce) heterojunction photocatalyst according to claim 1, characterized in that: The molar ratio of the bismuth source to the mannitol in the mannitol solution is 1:2-3; The molar ratio of the chlorine source to the mannitol in the mannitol solution is 1:0.6-1.
5. The method for preparing the BiOCl / UiO-66 (Zr / Ce) heterojunction photocatalyst according to claim 1, characterized in that: The UiO-66 (Zr / Ce) is prepared by the following steps: Terephthalic acid, a soluble cerium salt, a soluble zirconium salt and an acid are sequentially added into a solvent, and UiO-66 (Zr / Ce) is obtained through a solvothermal reaction.
6. The method for preparing the BiOCl / UiO-66 (Zr / Ce) heterojunction photocatalyst according to claim 5, characterized in that: The molar ratio of the soluble cerium salt, the soluble zirconium salt and terephthalic acid is 1:2:3-4; The usage ratio of terephthalic acid and solvent is 1 mol: 3 mL to 4 mL.
7. The method for preparing the BiOCl / UiO-66 (Zr / Ce) heterojunction photocatalyst according to claim 5, characterized in that: The soluble cerium salt is one of ammonium cerium nitrate and cerium chloride.
8. The method for preparing the BiOCl / UiO-66 (Zr / Ce) heterojunction photocatalyst according to claim 5, characterized in that: The soluble zirconium salt is one of zirconyl nitrate and zirconium chloride.
9. A BiOCl / UiO-66 (Zr / Ce) heterojunction photocatalyst prepared by the preparation method according to any one of claims 1 to 8.
10. An application of the BiOCl / UiO-66 (Zr / Ce) heterojunction photocatalyst as claimed in claim 9 in the field of photocatalysis, characterized in that: Application of photocatalytic degradation of tetracycline hydrochloride in water.